(untitled) (CIPEEX, 2022)
URINE IS AN IMPORTANT OBJECT OF STUDY TO ASSESS RENAL FUNCTION AND PROVIDE CLUES ABOUT THE ETIOLOGY OF DYSFUNCTIONS, BEING AN EASILY OBTAINABLE FLUID CAN REVEAL IMPORTANT INFORMATION ABOUT VARIOUS METABOLIC FUNCTIONS OF ORGANISMS. THE EXAMINATION OF ABNORMAL ELEMENTS OF URINARY SEDIMENTATION (EAS) INVOLVES THE ACCOMPLISHMENT OF THREE DISTINCT STAGES: PHYSICAL ANALYSIS, CHEMICAL ANALYSIS AND MICROSCOPIC ANALYSIS OF THE SEDIMENT. AFTER THE PHYSICAL AND CHEMICAL EXAMINATION THE URINARY SEDIMENT SHOULD BE OBSERVED BY MICROSCOPY. THE COMPONENTS OF URINARY SEDIMENT AS WELL AS THE RESULTS OF CHEMICAL AND PHYSICAL ANALYZES HAVE GREAT CLINICAL SIGNIFICANCE IN THE DIAGNOSIS AND MANAGEMENT OF PATIENTS. TO CARRY OUT THESE STEPS, EXTENSIVE EXPERIENCE IS REQUIRED FOR ACCURATE IDENTIFICATION AND CLASSIFICATION. THE OBJECTIVE OF THE PRESENT STUDY WAS TO ESTIMATE THE CHANGES PRESENT IN THE EAS EXAM IN SAMPLES OF PATIENTS ATTENDED IN A CLINICAL LABORATORY IN THE YEAR 2017. THE STUDY WAS CONDUCTED AT THE CLINICAL ANALYSIS LABORATORY OF UNIEVANGLICA LOCATED IN ANÁPOLIS - GOIS - BRAZIL. 500 URINE SAMPLES WERE PROCESSED ACCORDING TO THE RECOMMENDATIONS FOR THE URINE TEST ESTABLISHED BY THE BRAZILIAN ASSOCIATION OF TECHNICAL NORMS. STATISTICAL ANALYZES WERE PERFORMED THROUGH THE EPIINFO VERSION 3.5.1 PROGRAM. THE RESULTS OF THE PHYSICAL EXAMINATION INDICATED THE APPEARANCE VARIATION IN 170 SAMPLES, 34% (170/500) OF THE CASES AND 66% OF THE PHYSICAL EXAMINATIONS WERE CLEAR APPEARANCE (330/500), 24.20% WERE SLIGHTLY CLOUDY (121 / 500), AND ONLY 9.8% WERE CLOUDY (49/500). THE MOST PREVALENT STAINING WAS CITRUS YELLOW OBSERVED IN 78.60% (393/500) FOLLOWED BY 20.20% LIGHT YELLOW (101/500) AND OTHER COLORS 1.2% (6/500). SUI GENERIS ODOR WAS PRESENT IN 96% OF CASES (480/500), FETID URINE WAS REPORTED IN 4% OF CASES (INDICATIVE OF INFECTION). THE CHEMICAL TEST SHOWED BILIRUBIN WITH 97.4% ABSENT IN THE SAMPLES, 2.4% PRESENCE WITH A CROSS (+) AND 1 SAMPLES (0.20%) WITH TWO CROSSES (++).THE PRESENCE OF KETONE BODIES WAS ABSENT IN 98.4% OF THE SAMPLES, AND IN 5 SAMPLES, 1 (0%) AND 1 (0.20%) SAMPLES WERE OBTAINED, ) WITH TWO CROSSES. THE DENSITY PRESENTED VALUES €‹€‹IN VARIOUS SCALES, HIGH DENSITIES WERE VISUALIZED IN 11.8% (59/500). THE LEUKOCYTE ESTERASE IS INDICATIVE OF INFLAMMATION, THE TEST SHOWED THAT 10.2% (51/500) SAMPLES HAD THREE CROSSES (+++), 8.2% (41/500) SAMPLES HAD (+) AND 5.8% (29/500) OF THE SAMPLES HAD TWO CROSSES (++). THE ABSENCE OF LEUKOCYTE ESTERASE WAS OBSERVED IN 379 SAMPLES REPRESENTING 75.8%. GLYCOSURIA AND PROTEINURIA WERE OBSERVED IN 17 SAMPLES, REPRESENTING 3.4% EACH. THE NITRITE TEST THAT PREDICTS A URINARY TRACT INFECTION WAS PRESENT IN 9.8% OF THE SAMPLES. THE CHANGES PRESENT IN EAS ARE IN THE PHYSICAL EVALUATION OF THE SAMPLE, CHEMICAL AND SEDIMENTOSCOPIC, REVEALED IMPORTANT CLINICAL SIGNIFICANCE AND SERVING AS AN AID FOR INVESTIGATIONS OF VARIOUS METABOLIC AND RENAL DISEASES, AMONG OTHERS. IN THE EVALUATED POPULATION THE MAJORITY WAS WITHIN THE PARAMETERS OF NORMALITY THE PERFORMANCE OF THE TEST WAS SATISFACTORY TO DETERMINE PHYSICAL AND CHEMICAL ABNORMALITIES AND THE DIAGNOSIS OF INFECTIONS OF THE URINARY TRACT.